Experimental Investigation of Flow and Mechanical Properties of Fibrofor Fiber Reinforced Self-Compacting Concrete - Arun Kumar, H. R.; Shivakumaraswamy, B. (Asian Journal of Engineering and Applied Technology, 2019)
Self Compacting Concrete is a material used in the construction that has excellent deformability in the fresh state and high resistance of segregation, and can be replaced and compacted under its self-weight without applying vibration which leads to substantial advantages related to better homogeneity, enhancement of working environment and improvement in the productivity by increasing the speed of construction. Concrete can be formulated with high compressive strength but always has lower tensile strength. Tensile strength and other properties of concrete can be enhanced by adding fibers due to which the workability of concrete mix reduces and in order to achieve the desired Workability super-plasticizers is added. In the present work the use of fibrofor fiber in the production of self-compacting concrete (SCC) has been studied to identify how fresh and hardened properties of SCC are affected by the addition of fibers. The fibrofor fiber of 19mm standard length is incorporated into the SCC mixtures as 0.5kg/m3, 1.0kg/m3, 1.5kg/m3of concrete. Test on fresh SCC like slump Flow test, T50, V-Funnel test, J-Ring slump test and L-Box test were performed for an understanding of flow of SCC and tests on hardened properties like flexural strength, compressive strength and split tensile strength have been conducted to identify the hardened properties of SCC produced with fibrofor fiber. A comparative study between plain concrete, SCC without fiber and SCC with fiber has been done. Mix design for M40 grade concrete has been done according to EFNARC guidelines. The results reveal that the use of fibro for fiber decreases the workability but increases the mechanical properties of SCC. The optimum volume fraction of fibrofor fiber is determined as 1kg/m3 considering the optimized flexural strength and split tensile strength based properties of SCC. Due to increase in strength properties of fiber reinforced SCC that can be used for pavement construction and various other structures such as buildings, water retaining structures, reservoir structures and tunnel etc.